The Control of Corporate Europe 2002
DOI: 10.1093/0199257531.003.0004
|View full text |Cite
|
Sign up to set email alerts
|

Ownership and Voting Power in France

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 2 publications
3
23
0
1
Order By: Relevance
“…Table 2 provides insights into the ownership structures and the distribution of power among large shareholders. First of all and consistent with numerous previous studies (Bloch and Kremp, 2001;Faccio and Lang, 2002), France appears as a concentrated ownership country. Only 9.4% of the observations are widely held firms (i.e.…”
Section: Dependent and Control Variablessupporting
confidence: 91%
See 1 more Smart Citation
“…Table 2 provides insights into the ownership structures and the distribution of power among large shareholders. First of all and consistent with numerous previous studies (Bloch and Kremp, 2001;Faccio and Lang, 2002), France appears as a concentrated ownership country. Only 9.4% of the observations are widely held firms (i.e.…”
Section: Dependent and Control Variablessupporting
confidence: 91%
“…8 Here, this lack of accuracy does not stem from mistakes in the commercial databases (as mentioned by Dlugosz et al, 2006) but from the fact that French specificities of governance and ownership are not well taken into account. 9 About this mechanism, see also Bloch and Kremp (2001) and Ginglinger and Saddour (2006). 10 Results are available upon request.…”
Section: Footnotesmentioning
confidence: 99%
“…3 An extensive body of evidence has in fact confirmed that industry outcomes are affected by the financial status of market participants. 4 Building on this idea, a few recent theoretical papers have investigated whether internal capital markets established within business groups and multi-segment firms, by providing a source of financial slack to member units, may turn them into stronger competitors. 5 However, due to the lack of reliable data on corporate group structures, little work has empirically investigated whether and how access to internal capital markets affects a firm's competitive conduct.…”
mentioning
confidence: 99%
“…Becht and Röell (1999) provide a summary of the main findings of this network. For individual country studies see Becht and Böhmer (1999), , Bianchi et al (1999), Bloch and Kremp (1999), Crespí-Cladera and Garcia-Cestona (1999), De Jong et al (1999), Goergen and Renneborg (1999) and Gugler et al (1999).…”
Section: Ownership Structure and Corporate Governancementioning
confidence: 99%